World Breastfeeding Week 2024: An Intimate Breastfeeding Education Session with Working Mothers in BASF Indonesia - Dewanti, Lintang; Monica, Risda; Suri, Anggun; Larasati, Dewi (Lembaga Penelitian dan Publikasi Ilmiah, Yayasan Almahmudi Bin Dahlan, 2024)
The theme for WBW 2024,